Representations of the homosexuality in francophones literatures : between insults, silence, transvaluation and sexuality. areas of 'Le Flamant noir' of Berthrand Nguyen Matoko, '39 rue de Berne' (Max Lobe), 'Chuchote pas trop' and 'Portrait d'une jeu - (:unkn) unknown (My University, 2020)
By choosing to work on representations of homosexuality in French-speaking sub-Saharan African countries, we pursued three goals at our fingertips. Insurgency against the silence of several African scholars to address the theme of homosexuality in their scientific work, to make it our reflection has therefore imposed itself on us imperatively. Indeed, our first objective (epistemological) was to take an interest in this theme, which still remains an almost unexplored and untapped field of literature in French-speaking Africa, in order to reflect on the issues raised by this highly pregnant sexuality today. In other words, the disinterest or the lack of interest of a large number (of scholars) has undoubtedly drove in us an extra motivation whose result of this work can claim to be the echo. It should be noted that while fiction works abound, this is not the case for scientific work on the subject. The other aim, this time pragmatic, was to refute the idea that homosexuality is an exogenous sexuality to Africa. An idea that makes gay people more uncomfortable and feel apart because of their sexuality. As we have amply demonstrated in the light of Charles Guebogo's work, homosexuality is transcultural and therefore it has always existed among many African peoples. However, its current questioning is not that of past societies. Morals change with time, including men. It is therefore a conviction for us to (re)store self-esteem, trust and consideration to those people who are marginalized because of their sexual orientation. In doing so, we have emphasized acceptance, affirmation and self-representation of one's homosexuality. The last goal is much more personal and it aims at satisfying an intellectual curiosity. Why does this sexuality arouse so much debate these days, divide families or homes in some countries, yet so insignificant in Greek antiquity? Is homosexuality only a sexual act between two or more people of the same sex or does it go beyond geni
Keywords: African Research